Raloxifene enhances peri-implant bone healing in osteoporotic rats - Ramalho-Ferreira, G. [UNESP]; Faverani, L. P. [UNESP]; Prado, F. B.; Garcia, I. R. [UNESP]; Okamoto, R. [UNESP] (Churchill Livingstone, 2015)
The aim of this study was to evaluate bone healing at the bone implant interface in rats with induced osteoporosis. The rats underwent a bilateral ovariectomy (OVX) and were fed a low calcium and phosphate diet. The OVX rats were divided into three groups: one was treated with raloxifene (OVX-RAL), one with alendronate (OVX-ALE), and one received no medication (OVX-NT). The control group rats (SHAM-DN) underwent sham surgery and were fed a normal diet. Each animal received one implant in each tibia: a machined surface implant in the right tibia and an implant with surface etching in the left tibia. All animals were euthanized after 42 days. Analysis of variance (ANOVA) and Tukey post hoc tests were applied to the biomechanics (reverse torque) and bone implant contact (BIC) data (P < 0.05). The RAL and ALE groups showed improved pen-implant bone healing. However, the ALE group showed no significant difference from the OVX-NT group. Surface treatment promoted higher corticalization at the bone implant interface, but showed the same characteristics of mature bone and bone neoformation in concentric laminations as the machined implant. There were no statistically significant differences in reverse torque (P = 0.861) or BIC (P = 0.745) between the OVX-RAL and SHAM-DN groups. Therefore, the use of raloxifene resulted in good biomechanical, BIC, and histological findings in the treatment of induced osteoporosis in rats.
Keywords: alendronate; raloxifene; osteoporosis